2016
DOI: 10.1126/science.aaf9286
|View full text |Cite
|
Sign up to set email alerts
|

Achieving global targets for antimicrobial resistance

Abstract: Supplemental Materials asfasfasfsdfafafafafsdafafafafafasf FIGURE. CAPTION. Based on (8). See SM. Commented [BW2]: We need a brief caption. There likely will not be room for caption text to explain/interpret/analyze the data. Instead, it just needs to give the basic info needed to interpret the axes, data source, etc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
167
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(177 citation statements)
references
References 14 publications
1
167
0
3
Order By: Relevance
“…Antimicrobial resistance (AMR) driven by inappropriate use of antimicrobial agents has become a global health problem in recent years (Dryden 2017;Laxminarayan et al 2016;Marston et al 2016;WHO 2002). The problem of these multidrug resistance and undesirable side effects of most antibiotics necessitate the search for new antimicrobial agents of plant origin.…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial resistance (AMR) driven by inappropriate use of antimicrobial agents has become a global health problem in recent years (Dryden 2017;Laxminarayan et al 2016;Marston et al 2016;WHO 2002). The problem of these multidrug resistance and undesirable side effects of most antibiotics necessitate the search for new antimicrobial agents of plant origin.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that macrolide use promoted a marked increase in macrolide resistance of the microbiota [15]. And worse still, abuse and misuse of antibiotics make antibiotic resistance give birth to the 'super bacteria' [57,58]. In one study on Mycobacterium tuberculosis, the causative agent of tuberculosis, Warrier et al [59] have discovered a novel bacterial drug resistance, antibiotic inactivation via N-methylation.…”
Section: Brief Summary and Future Prospectsmentioning
confidence: 99%
“…New opportunities are emerging, such as the Cape Town agreement signed in 2001 (where several stakeholders agreed to improve research and development in the TB field [32,33]) or the recent plan of the United Nations on antimicrobial resistance (focused on a global strategy to mitigate the antimicrobial resistance burden [34]) to impact the MDR-TB epidemic.…”
mentioning
confidence: 99%